Mapping and understanding the distributions of potential vector mosquitoes in the UK: New methods and applications - Golding, N (2013)
A number of emerging vector-borne diseases have the potential to be transmitted in the UK by native mosquitoes. Human infection by some of these diseases requires the presence of communities of multiple vector mosquito species. Mitigating the risk posed by these diseases requires an understanding of the spatial distributions of the UK mosquito fauna. Little empirical data is available from which to determine the distributions of mosquito species in the UK. Identifying areas at risk from mosquito-borne disease therefore requires statistical modelling to investigate and predict mosquito distributions. This thesis investigates the distributions of potential vector mosquitoes in the UK at landscape to national scales. A number of new methodological approaches for species distri- bution modelling are developed. These methods are then used to map and understand the distributions of mosquito communities with the potential to transmit diseases to humans. Chapter 2 reports the establishment of substantial populations of the West Nile virus (WNV) vector mosquito Culex modestus in wetlands in southern England. This represents a drastic shift in the species’ known range and an increase in the risk of WNV transmission where Cx. modestus is present. Chapter 3 develops and applies a new species interaction distribution model which identifies fish and ditch shrimp of the genus Palaemonetes as predators which may restrict the distribution of the potential WNV vector community in these wetlands. Chapter 4 develops a number of methods to make robust predictions of the probability of presence of a species from presence-only data, by eliciting and applying estimates of the species’ prevalence. Chapter 5 introduces a new Bayesian species distribution modelling approach which outperforms existing methods and has number of useful features for dealing with poor- quality data. Chapter 6 applies methods developed in the previous two chapters to produce the first high-resolution distribution maps of potential vector mosquitoes in the UK. These maps identify several wetland areas where vector communities exist which could maintain WNV transmission in birds and transmit it to humans. This thesis makes significant contributions to our understanding of the distributions of UK mosquito species. It also provides methods for species distribution modelling which could be widely applied in ecology and epidemiology.